How Does AI Impact Healthcare Worker Employment? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is rapidly becoming an integral part of the healthcare landscape, promising to revolutionize everything from diagnostics to pati...
Keywords: AI Ethics in Healthcare; Impact; Healthcare; Worker; Artificial Intelligence; Diagnostics; Patient Care